Women's Resistance in Facing the Patriarchal Domination of Fathers in the Film Text Bolehkah Sekali Saja Kumenangis - Radhina Maryam; Fafi Inayatillah (Raja Zulkarnain Education Foundation, 2026)
Bolehkah Sekali Saja Kumenangis is an Indonesian drama film released on October 17, 2024, directed by Reka Wijaya and written by Junisya Aurelita, Rezy Junio, Santy Diliana, and Alim Sudio. The film is inspired by the song Runtuh, popularized by Feby Putri and Fiersa Besari in 2021. This study aims to: 1) analyze the representation of the father’s patriarchal dominance in the film Bolehkah Sekali Saja Kumenangis, 2) identify the form of existential resistance of female characters against the father’s patriarchal dominance in the domestic sphere based on the perspective of Simone de Beauvoir’s existentialist feminism, and 3) explain the process of the female character’s transcendence from the position of The Other to the existential subject according to Simone de Beauvoir. This research was conducted in 2026 at Surabaya State University. The research population was all scenes and dialogue texts in the film Bolehkah Sekali Saja Kumenangis by Reka Wijaya, with samples in the form of scenes and dialogues that represent the father’s patriarchal dominance, existential resistance, and the process of the female character’s transcendence. The research instrument was a human instrument (the researcher herself) assisted by a data classification table. The data analysis tool used the Miles and Huberman model consisting of data reduction, data presentation, and drawing conclusions. The results of the study show three main findings. First, the father’s patriarchal dominance is represented through four forms: structural, psychological, verbal, and restrictions on movement. Second, the female characters’ existential resistance takes the form of active resistance, with Tari demonstrating resistance from the beginning of the film and Ibu at the climax. Third, the female characters’ process of transcendence from the position of The Other, the process of transcendence, and existential freedom.